Media Big Book Alphabet Recognition in Early Childhood - Nihayatul Mazidah; Khamim Zarkasih Putro; Naimah Naimah; Suyadi Suyadi; Syariful Anam (AL-ISHLAH: Jurnal Pendidikan, 2023)
Students at kindergarten can learn the alphabet through a Big Book-based lesson. It helps them master the alphabet. The goals of this research are to (1) determine the extent to which Big Book media are being used to teach the alphabet in kindergarten, (2) examine the ways in which teachers are using Big Book media to teach the alphabet, and (3) draw conclusions about the implications of utilising Big Book media to teach students to recognise individual letters. Because kindergarteners often struggle to recognise and recall the alphabet, teachers often resort to Big Book media. To aid children's memorisation and speed with letter recognition, the Big Book includes a section devoted to the alphabet.  Qualitative methods of description were used in this investigation. Observation, interviews, and thorough documentation are the backbone of the data collection process. The three phases of data analysis are reducing data, presenting data, and making conclusions. The study's findings suggest that (1) Big Book media improves children's letter recognition when compared to other media. (2) In this kindergarten, teachers use Big Book media for teaching letter recognition since it is more engaging and straightforward for young students. Three implications of Big Book media, which is used as a medium to teach kids the alphabet in kindergarten, based on markers of progress towards quicker and easier letter recognition.